Corticosteroids and obesity in steroid-sensitive and steroid-resistant nephrotic syndrome - Nina Lestari; Neti Nurani; Madarina Julia (Paediatrica Indonesiana, 2015)
Background Children with nephrotic syndrome need high-dose corticosteroids to achieve remission. Studies have estimated a 35-43% risk of obesity in these patients after corticosteroid treatment.Objective To determine the prevalence of obesity in children who received corticosteroids for nephrotic syndrome, and to compare the risk of obesity in children with steroid-sensitive nephrotic syndrome (SSNS) and steroid-resistant nephrotic syndrome (SRNS).Methods We performed a retrospective cohort study in 50 children with SSNS or SRNS who received corticosteroid treatment. Obesity was defined to be a BMI-for-age Z-score above +2.0 SD, according to the WHO Growth Reference 2007. Central obesity was defined to be a waist-to-height ratio > 0.50.Results The overall prevalence of obesity was 22%, with 29% and 14% in the SSNS and SRNS groups, respectively. The overall prevalence of central obesity was 50%, with 54% and 46% in the SSNS and SRNS groups, respectively. The cumulative steroid doses in this study were not significantly different between the SSNS and SRNS groups. There were also no significant differences between groups for risk of obesity (RR 2.53; 95%CI 0.58 to 10.99) or central obesity (RR 1.39; 95%CI 0.45 to 4.25).Conclusion In children with nephrotic syndrome who received corticosteroids, the prevalence of obesity is 22% and of central obesity is 50%. In a comparison of SSNS and SRNS groups, cumulative steroid dose as well as risks of obesity and central obesity do not significantly differ between groups.